At three years, patients with acute lymphoblastic leukaemia are still at risk for relapse. Results of the international MRC UKALLXII/ECOG E2993 trial. (27th March 2020) - Ganzel, Chezi; Wang, Xin V.; Rowe, Jacob M.; Richards, Susan M.; Buck, Georgina; Marks, David I.; Litzow, Mark R.; Paietta, Elisabeth M.; Foroni, Letizia; Luger, Selina M.; Willman, Cheryl L.; Mullighan, Charles G.; et al.
Summary: Late relapse [>3 years from complete remission (CR)] in acute lymphoblastic leukaemia (ALL), is unusual. Data from the MRC UKALLXII/ECOG E2993 trial are presented to evaluate the incidence and characteristics of late relapse in adult ALL. Of 1, 909 patients, 1, 752 (92%) achieved CR and among these 757 (43·2%) relapsed; 691 (91·3%) within three years and 66 (8·7%) beyond. Among these 66 patients, median time to relapse was 47 (37–144) months. Relapse beyond three years occurred in 3·8% of all who achieved CR. The cumulative risk of relapse was 40%, 43% and 45% at three, five and ten years respectively. Out of the 1 752 patients who achieved CR, 11·7% underwent autologous and 40·6% allogeneic transplant, while in CR1. Of the autologous patients, 43·2% relapsed early and 3·4% relapsed late. However, among the allogeneic patients, 13·2% relapsed early and only 1·3% late. The five‐year overall survival from relapse was 5·8% and 20% in the early and late relapse patients respectively. In conclusion, late relapse in adults with ALL is not uncommon, and is associated with better outcome after relapse compared to early relapse.